Outsourcing Tariff Evasion : A New Explanation for Entrepot Trade. (IMF Working Papers; Working Paper ;, 2005)
Traditional explanations for indirect trade carried out through an entrepot have focused on savings in transport costs and on the role of specialized agents in processing and distribution. We provide an alternative perspective based on the possibility that entrepots may facilitate tariff evasion. Using data on direct exports to mainland China and indirect exports to it via Hong Kong SAR, we find that the indirect export rate rises with the Chinese tariff rate, even though there is no legal tax advantage to sending goods via Hong Kong SAR. We undertake a number of extensions to rule out plausible alternative hypotheses.